Characteristics of the Urinary Microbiome From Patients With Gout: A Prospective Study - Ning, Yaogui; Yang, Guomei; Chen, Yangchun; Zhao, Xue; Qian, Hongyan; Liu, Yuan; Chen, Shiju; Shi, Guixiu (Frontiers in Endocrinology, 2020)
The role of host microbes in the pathogenesis of several diseases has been established, and altered microbiomes have been related to diseases. However, the variability of the urinary microbiome in individuals with gout has not been evaluated to date. Therefore, we conducted the present prospective study to characterize the urinary gut microbiome and its potential relation to gout. Urine samples from 30 patients with gout and 30 healthy controls were analyzed by Illumina Miseq sequencing of the 16S rRNA hypervariable regions, and the microbiomes were compared according to alpha-diversity indices, complexity (beta-diversity) with principal components analysis, and composition with linear discriminant analysis effect size. The most significantly different taxa at the phylum and genus levels were identified, and their potential as biomarkers for discriminating gout patients were assessed based on receiver operating characteristic curve (ROC) analysis. Compared to the healthy controls, there was a dramatic decrease in microbial richness and diversity in the urine of gout patients. The phylum Firmicutes and its derivatives (Lactobacillus_iners, Family_XI, and Finegoldia), the phylum Actinobacteria and its derivatives (unidentified_ Actinobacteria, Corynebacteriales, Corynebacteriale, Corynebacterium_1, and Corynebacterium_tuberculostearicum), and the genera Prevotella and Corynebacterium_1 were significantly enriched in the urine of gout patients. ROC analysis indicated that the top five microbial genera could be reliable markers to distinguish gout patients from healthy individuals. These findings demonstrate that there are specific alterations in the microbial diversity of gout patients. Thus, further studies on the causal relationship between gout and the urinary microbiome will offer new prospects for diagnosing, preventing, and treating gout.